Clinical Evaluation of Biotrue Hydration Plus Multipurpose Solution in Daily Use with Planned Replacement Soft Contact Lenses - Mark Schaeffer; Ayda Shahidi; Gary Mosehauer; Marjorie Rah; William Reindel (Ophthalmology and Therapy)
Abstract Introduction Planned replacement soft contact lenses (PRSCLs) continue to remain a popular option for vision correction. Biotrue Hydration Plus (BHP) is a novel multipurpose solution (MPS) developed for PRSCLs, with a formulation informed by Tear Film & Ocular Surface Society (TFOS) International Dry Eye Workshop II insights. It contains hyaluronan (HA) for moisturizing, erythritol for antioxidant and osmoprotectant properties, and potassium to support ocular homeostasis. It also incorporates poloxamine 1107 and poloxamer 181 surfactants for lens cleaning and wettability, alongside a triple disinfectant system. A two-arm study evaluated the clinical performance of BHP MPS over 3 months; here, we present a subanalysis of the BHP MPS arm. Methods This study was conducted across 17 sites in the USA, with evaluations at 2 weeks, 1 month, 2 months, and 3 months of lens wear. BHP MPS was dispensed to habitual wearers of silicone hydrogel or conventional hydrogel PRSCLs (four and one prespecified types, respectively). Subjects rated 13 lens performance attributes (grouped into comfort, vision, handling, lens cleanliness, and overall impression). Performance ratings were compared across visits using statistical methods to confirm consistency and equivalence. Investigators performed slit lamp examinations and evaluated lens deposits at each follow-up visit to assess MPS biocompatibility. Results Mean scores for lens comfort, vision, handling, and cleanliness on removal, and also overall impression, were 80–100 across all visits (very good–excellent; p ≥ 0.05). No subject presented with > Grade 2 slit lamp findings at any visit, and few ungraded slit lamp findings were noted, reflecting the biocompatibility of BHP MPS with respect to the ocular surface. Lens deposition, cleanliness, and wettability were clinically acceptable in almost all subjects, and no participants discontinued owing to an adverse event. Conclusions In this analysis, BHP MPS was associated with minimal lens deposition, excellent biocompatibility, and high-performance ratings, making it a promising option for PRSCL wearers and for eye care practitioners to recommend before switching symptomatic wearers to a different contact lens modality. Trial Registration ClinicalTrials.gov identifier NCT03897751.